Pendampingan dalam Proses Peningkatan Potensi Kreatifitas dari Anak-Anak Berkebutuhan Khusus - Khairunnisa; Dewa Ayu Oki Astarini; Defel Septian; Ni Ketut Sriwinarti; Ikang Murapi (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
A special school is a special institution that provides educational services to people who have special needs. Special schools are a form of equalization by providing equal opportunities to all people so that these special schools are able to accommodate the future and aspirations of people who have limitations. Different physical and mental conditions make people with special needs also have different treatment in the community. Psychologically, those with special needs need more attention than people in general. This activity is a form of humanity that aims to introduce the community more specifically to students to increase social feeling, as a form of caring and sharing enthusiasm for extraordinary friends, as well as helping provide assistance and encouragement to increase creativity for children with special needs. The method used is fun learning. Activities in this service contribute to development which has an impact on increasing the ability to be creative, even though in carrying out a series of activities the service team has difficulties in communicating with extraordinary friends.